Human Antibodies to VP4 Inhibit Replication of Enteroviruses Across Subgenotypes and Serotypes, and Enhance Host Innate Immunity - Phanthong, Siratcha; Densumite, Jaslan; Seesuay, Watee; Thanongsaksrikul, Jeeraphong; Teimoori, Salma; Sookrung, Nitat; Poovorawan, Yong; Onvimala, Napa; Guntapong, Ratigorn; Pattanapanyasat, Kovit; Chaicumpa, Wanpen (Frontiers in Microbiology, 2020)
Hand, foot, and mouth disease (HFMD) is a highly contagious disease that usually affects infants and young children (<5 years). HFMD outbreaks occur frequently in the Asia-Pacific region, and these outbreaks are associated with enormous healthcare and socioeconomic burden. There is currently no specific antiviral agent to treat HFMD and/or the severe complications that are frequently associated with the enterovirus of serotype EV71. Therefore, the development of a broadly effective and safe anti-enterovirus agent is an existential necessity. In this study, human single-chain antibodies (HuscFvs) specific to the EV71-internal capsid protein (VP4) were generated using phage display technology. VP4-specific HuscFvs were linked to cell-penetrating peptides to make them cell-penetrable HuscFvs (transbodies), and readily accessible to the intracellular target. The transbodies, as well as the original HuscFvs that were tested, entered the enterovirus-infected cells, bound to intracellular VP4, and inhibited replication of EV71 across subgenotypes A, B, and C, and coxsackieviruses CVA16 and CVA6. The antibodies also enhanced the antiviral response of the virus-infected cells. Computerized simulation, indirect and competitive ELISAs, and experiments on cells infected with EV71 particles to which the VP4 and VP1-N-terminus were surface-exposed (i.e., A-particles that don’t require receptor binding for infection). Overall results indicate that the VP4-specific antibodies inhibit virus replication by interfering with the VP4-N-terminus, which is important for membrane pore formation and virus genome release leading to less production of virus proteins, less infectious virions, and restoration of host innate immunity. The antibodies may inhibit polyprotein/intermediate protein processing and cause sterically strained configurations of the capsid pentamers, which impairs virus morphogenesis. These antibodies should be further investigated for application as a safe and broadly effective HFMD therapy.